Responsive Feeding Ibu Dengan Kejadian Stunting Pada Upaya Perlindungan Anak di Kecamatan Moyudan, Sleman Yogyakarta - Mufdlilah Mufdlilah; Tri Hapsari Listyaningrum; Agung Nugroho; Dyah Ayu Fitriani; Hairiana Kusvitasari; Nur Laeli Rokhmah (Jurnal Pelayanan dan Pengabdian Masyarakat (Pamas), 2023)
Stunting is a major nutritional problem in Indonesia. Children are chronically malnourished and appear too short. The causes of stunting problems are lack of knowledge and attitudes towards responsive feeding, lack of nutritional intake, and wrong parenting patterns for toddlers. This community service aims to increase the knowledge and attitudes of mothers about responsive feeding. The implementation of this community service through health promotion activity was counseling. This activity has been t in October 2021 at the At-Taqwa Mosque in Sangubanyu village, involving six mothers. The results of community service activities showed an increase in mothers' knowledge about responsive feeding from 66.7% to 100%. The mother's attitude increased after being given counseling from 33.3% to 66.7%. Efforts to increase knowledge and attitudes are providing education about responsive feeding counseling through program integration activities at the Aisyiyah Moyudan Primary Clinic. The outputs of community service activities carried out are in the form of a scientific article, an electronic media article on the website of the Universitas ‘Aisyiyah Yogyakarta, a booklet on responsive feeding, and an HKI booklet on responsive feeding. Keywords: responsive feeding; stunting